Digital Health Literacy About COVID-19 as a Factor Mediating the Association Between the Importance of Online Information Search and Subjective Well-Being Among University Students in Vietnam - Linh Hoang Thuy Nguyen; Linh Hoang Thuy Nguyen; Man Thi Hue Vo; Lien Thi Mai Tran; Kevin Dadaczynski; Kevin Dadaczynski; Orkan Okan; Linda Murray; Thang Van Vo; Thang Van Vo (Frontiers Media S.A., 2021)
Introduction: Digital health literacy (DHL) has recently been proposed as a means of enabling healthy decisions for protective behavior, preventive measures, and adherence with COVID-19 policies and recommendations especially in the era of the "infodemic". This study aimed to (1) identify COVID-19 related DHL and its association with online information seeking; (2) to elucidate COVID-19 related DHL as a mediator predictor between the importance of online information search and its association with subjective well-being among Vietnamese university students.Methods: A cross-sectional web-based survey was used to elicit the responses of Vietnamese students over 2 consecutive weeks (from April 25 to May 9, 2020, n = 1,003, 70.1% female students, mean age 21.4 ± 3.1). The online survey questionnaire collected data on the sociodemographic characteristics of participants, DHL about COVID-19, information seeking behavior, and subjective well-being. Mediation analysis was conducted using the importance of searching COVID-19 related information as independent variables, subjective well-being as a dependent variable, and DHL as a mediator variable.Results: Among 1,003 students, the mean (SD) of DHL related to COVID-19 was 2.87 ± 0.32. In the survey, 87.2% of the students reported sufficient well-being, while almost 13% reported low or very low well-being. The findings also indicated that search engines were the most popular platform for information seeking by Vietnamese students (95.3%) and 92.8% of participants had searched for information related to the current spread of COVID-19. Not searching for hygiene regulation as part of infection control and an average level of information satisfaction were associated with limited DHL (p < 0.05). The importance of online information searching related to COVID-19 increased the subjective well-being of students significantly and limited DHL (p < 0.05). DHL was found to mediate the relationship between the importance of online information searching and the subjective well-being of students.Conclusion: The finding provides insight into DHL about COVID-19 among university students, and their ability to find, understand, appraise, and use online health related information during lockdown throughout the first COVID-19 pandemic wave. DHL should be highlighted as a mediating factor that enhances the positive effect of the importance of information seeking on psychological well-being. However, further studies are needed to better define the mediating role of DHL across other factors.